2002
DOI: 10.1063/1.1477186
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics in plastic crystals

Abstract: We report dielectric data on six different plastic crystalline materials, namely 1-cyanoadamantane, adamantanone, pentachloronitrobenzene, cyclo-hexanol, ethanol, and meta-carborane, covering a frequency range of up to 14 decades and up to 20 GHz. Information on phase transitions, the α-relaxation, and relaxation processes beyond the α-relaxation are provided. The α-relaxation shows clear non-Debye behavior and varying degrees of deviation from thermally activated behavior. Our results reveal a generally rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
366
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(399 citation statements)
references
References 122 publications
31
366
0
2
Order By: Relevance
“…Nonetheless, recent studies on compounds such as ethanol and glutaronitrile, which depending on the thermal treatment display (at the same temperature) either a plastic crystalline state or a supercooled liquid phase, have shown 27,36 that the characteristic diffusional frequency in the supercooled liquid is at all temperatures very close to that of reorientational motions in the plastic crystal. Our findings are therefore a further confirmation of the idea that the dynamics of glassforming systems is fundamentally determined by rotational motions; 27,[36][37][38][39][40] while the connection between translational and rotational timescales was until now only based on the observation of similar but not identical temperature dependence and frequency ranges in different phases, we report here a perfect correlation of translational and rotational degrees of freedom in the same phase. The correspondence of σ dc and f max originates because both quantities are fundamentally linked to the diffusion of molecular species between lattice defects, which can be thought to be limited by an effective "diffusional" viscosity η diff .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, recent studies on compounds such as ethanol and glutaronitrile, which depending on the thermal treatment display (at the same temperature) either a plastic crystalline state or a supercooled liquid phase, have shown 27,36 that the characteristic diffusional frequency in the supercooled liquid is at all temperatures very close to that of reorientational motions in the plastic crystal. Our findings are therefore a further confirmation of the idea that the dynamics of glassforming systems is fundamentally determined by rotational motions; 27,[36][37][38][39][40] while the connection between translational and rotational timescales was until now only based on the observation of similar but not identical temperature dependence and frequency ranges in different phases, we report here a perfect correlation of translational and rotational degrees of freedom in the same phase. The correspondence of σ dc and f max originates because both quantities are fundamentally linked to the diffusion of molecular species between lattice defects, which can be thought to be limited by an effective "diffusional" viscosity η diff .…”
Section: Resultsmentioning
confidence: 99%
“…Panels (a) and (b) of Figure 2 highlight the need of two dipolar processes (displayed as dotted lines) for modelling the dielectric spectra. It should be noticed that in previous work 19,40 only one HN function was employed to fit the loss curves, and this resulted in a slight discrepancy between the experimental data and the fit function in the high-frequency range of the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…33 As far as orientationally disordered materials are concerned, an earlier work 18 based on the comparison of several OD phases concluded that the EW is absent and thus not a universal feature of such glass formers. However, few years later the same authors reported 19 the possible existence of an EW in PCNB. The phase behaviour of this molecule, which forms a layered structure of triangular planes, has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations